2020
DOI: 10.1186/s12916-020-1502-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the burden of iron deficiency among African children

Abstract: Background: Iron deficiency (ID) is a major public health burden in African children and accurate prevalence estimates are important for effective nutritional interventions. However, ID may be incorrectly estimated in Africa because most measures of iron status are altered by inflammation and infections such as malaria. Through the current study, we have assessed different approaches to the prediction of iron status and estimated the burden of ID in African children. Methods:We assayed iron and inflammatory bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 32 publications
(37 reference statements)
4
66
1
Order By: Relevance
“…Gebreegziabher et al [ 17 ] reported the same situation in rural southern Ethiopia among women of reproductive age. By contrast, Muriuki et al investigated iron prevalence across five countries in Africa [ 18 ] and found a much higher pooled prevalence of ID, 34.3%. The difference might be due to the high prevalence of malaria and inflammation in our population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gebreegziabher et al [ 17 ] reported the same situation in rural southern Ethiopia among women of reproductive age. By contrast, Muriuki et al investigated iron prevalence across five countries in Africa [ 18 ] and found a much higher pooled prevalence of ID, 34.3%. The difference might be due to the high prevalence of malaria and inflammation in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Motadi et al [ 19 ] also found a much higher prevalence according to TSAT (12%) than adjusted ferritin (2.3%). Moreover, Muriuki et al [ 18 ] reported that TSAT is the most sensitive and specific marker compared to the gold standard, which is regression with adjusted ferritin in African children. Dignass et al [ 20 ] also suggested the use of TSAT rather than ferritin in the context of chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is defined as hemoglobin levels below 11 g/dL in children 6-50 months, and below 11.5 g/dL in children aged over 5 years (WHO 2018(WHO , 2011. It was estimated that about half of all anemia is attributable to iron deficiency depending on the geographic and disease environment (Darnton-Hill and Mkparu 2015), but recent studies show that the prevalence of iron deficiency is underestimated in African children, and is much lower than that of anemia (Lemoine and Tounian 2020;Muriuki et al 2020). In fact, ferritin is a good indicator of the body's iron stores, but it is not a specific reflection, with both inflammation and infection causing an increase: the use of transferrin saturation may provide a more accurate approach (Muriuki et al 2020).…”
Section: Iron Deficiencymentioning
confidence: 99%
“…It was estimated that about half of all anemia is attributable to iron deficiency depending on the geographic and disease environment (Darnton-Hill and Mkparu 2015), but recent studies show that the prevalence of iron deficiency is underestimated in African children, and is much lower than that of anemia (Lemoine and Tounian 2020;Muriuki et al 2020). In fact, ferritin is a good indicator of the body's iron stores, but it is not a specific reflection, with both inflammation and infection causing an increase: the use of transferrin saturation may provide a more accurate approach (Muriuki et al 2020). Accurate epidemiological data on the prevalence of iron deficiency are difficult to obtain due to the many compounding factors, especially infections and general inflammation (Lemoine and Tounian 2020).…”
Section: Iron Deficiencymentioning
confidence: 99%
See 1 more Smart Citation